The Effect of Company's Life Cycle, and Related Party Transactions on Profits Quality and Their Impact on Firm Value - Susanto, Andre; Daito, Apollo (Eduvest - Journal of Universal Studies, 2023)
This study aims to determine the effect of company's life cycle and related party transactions on earnings quality and its impact on firm value. This type of research is quantitative research. This study uses secondary data obtained from the Indonesian Stock Exchange (IDX) website. The sample for this research was 18 companies that carried out IPOs for the 2018-2021 period. This study used a purposive sampling technique as a sample selection. The analytical method of this study uses multiple linear regression analysis with Eviews 11 as an analytical tool. The results of study show company's life cycle affects earnings quality, while related party transactions do not affect earnings quality. The company's life cycle and related party transactions affect the firm’s value. Earnings quality has a significant effect on firm value. Earnings quality is capable of mediating between the company's life cycle and related party transactions with firm value.